HIF-1α contributes to proliferation and invasiveness of neuroblastoma cells via SHH signaling. - Sheng Chen; Min Zhang; Lili Xing; Yue Wang; Yongtao Xiao; Yeming Wu (PLoS ONE)
The aim of this study was to investigate the effects of hypoxia-inducible factor-1α (HIF-1α) on the proliferation, migration and invasion of neuroblastoma (NB) cells and the mechanisms involved. We here initially used the real-time polymerase chain reaction (real-time PCR), Western blotting and immunohistochemistry (IHC) to detect the expression of HIF-1α and components of the sonic hedgehog (SHH) signaling pathway in NB cells and human specimens. Subsequently, cell proliferation, migration and invasion were analyzed using the cell counting assay, wound healing assay and Transwell system in two types of human NB cell lines, SH-SY5Y and IMR32. In addition, the role of HIF-1α in NB cells growth was determined in a xenograft nude mouse model. We found that the level of HIF-1α was significantly upregulated during NB progression and was associated with the expression of two components of SHH signaling, SHH and GLI1. We next indicated that the proliferation, migration and invasiveness of SH-SY5Y and IMR32 cells were significantly inhibited by HIF-1α knockdown, which was mediated by small interfering RNAs (siRNAs) targeting against its mRNA. Furthermore, the growth of NB cells in vivo was also suppressed by HIF-1α inhibition. Finally, the pro-migration and proliferative effects of HIF-1α could be reversed by disrupting SHH signaling. In conclusion, our results demonstrated that upregulation of HIF-1α in NB promotes proliferation, migration and invasiveness via SHH signaling.